Accessibility in Enterprise Resource Planning systems: Who is Responsible For It and What Are the Main Difficulties to Put It Into Practice? - Guissoni, Ellen Diana Silva de Carvalho; Freire, André Pimenta; Araújo, Rafael Dias (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: Enterprise Resource Planning (ERP) systems have become increasingly important for companies to support their processes. Appropriate accessibility to information systems, especially ERPs, is essential to provide people with disabilities with the right to work and be active citizens. Problem: The lack of knowledge on the subject of Web accessibility is huge, and its inclusion in the ERP systems development process is still limited. Solution: Thus, this work aims at evaluating accessibility issues in ERP systems, by analyzing different levels of knowledge on the subject among stakeholders of the development process of this type of software. Theoretical approach: The study drew upon pre- and post-intervention diagnostic procedures based on the Theory of Planned Behaviour. The intervention used a Design Thinking-based approach. Method: This research used an exploratory approach for quantitative and qualitative analysis of data collected in a Design Thinking workshop with 17 people working in an ERP development company. Results: Data analysis showed that participants agreed that, despite their lack of information on the topic of web accessibility, it is an extremely important issue for social inclusion. They also pointed out that implementing accessibility was considered less complex or costly than they had expected. They understood that there is considerable added-value in a Web product when it is accessible. Contributions and Impact in the IS area: The results from this study provide valuable contributions to the understanding of factors that may help improve the accessibility of ERP systems. It can also help promote the inclusion of people with disabilities who work for companies that employ such systems.